Labor Law Implications of the Use of Artificial Intelligence on Employment in Indonesia as a Developing Country - Raffi Ikzaaz Abdallah; Kaharuddin Kaharuddin (Green Publisher Indonesia, 2026)
This study examines the legal implications of Artificial Intelligence (AI) adoption in professional employment sectors in Indonesia and compares them with regulatory frameworks in the United States. As a developing nation operating under a civil law system, Indonesia has yet to establish comprehensive regulations capable of responding to the disruptions AI poses to labor stability and job availability. Existing labor legislation and electronic systems regulations do not sufficiently protect workers from the risks of automation or AI-driven termination of employment. In contrast, the United States, through Federal Executive Order No. 14110 (2023) and the Automated Employment Decision Tools Law (2021), has established adaptive regulatory mechanisms emphasizing independent audits, transparency in AI utilization, and the protection of civil rights and employment equity. The findings indicate that Indonesia must develop more responsive AI governance within its labor regulatory framework, including limiting the use of AI in recruitment, restricting AI-based efficiency layoffs, and implementing clear accountability standards for AI providers. These conclusions highlight the need for labor law reform to balance technological advancement with worker protection in the digital era.​